Ceramic components, cutting inserts, and cutting tools

By incorporating a NaCl-type crystal structure coating layer with a peak intensity ratio of 1.0 or more in ceramic cutting tools, the adhesion between the substrate and coating layer is improved, enhancing the durability of cutting inserts and tools to handle increased machining loads.

JP7669127B2Active Publication Date: 2025-04-28NITERRA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020147365
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-02
Publication Date
2025-04-28
Estimated Expiration
2040-09-02

AI Technical Summary

Technical Problem

The increasing load on cutting tools in machining has necessitated improved adhesion between the substrate and the coating layer in ceramic members to enhance durability.

Method used

A ceramic member with a substrate containing alumina and tungsten carbide, and a coating layer with a NaCl-type crystal structure, specifically titanium nitride, where the peak intensity ratio (IA/IB) of X-ray diffraction peaks is 1.0 or more, improving adhesion.

Benefits of technology

The enhanced adhesion between the substrate and the coating layer results in improved durability of cutting inserts and tools, effectively handling increased loads in machining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669127000003
    Figure 0007669127000003
  • Figure 0007669127000004
    Figure 0007669127000004
  • Figure 0007669127000005
    Figure 0007669127000005
Patent Text Reader

Abstract

To improve adhesion between a substrate and a coating layer.SOLUTION: There is provided a ceramic member comprising a substrate containing alumina and tungsten carbide, and a coating layer which is formed on the surface of the substrate and is formed of a chemical compound having a crystal structure of a NaCl type. The ceramic member is characterized in that the value of a peak intensity ratio (IA / IB) is not lower than 1.0, provided that IA is a peak intensity assigned to a (111) plane of the chemical compound, and IB is a peak intensity assigned to a (200) plane of the chemical compound, when measuring the coating layer by X-ray diffraction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a ceramic member, a cutting insert, and a cutting tool. [Background technology]

[0002] Patent Document 1 discloses a ceramic member made of alumina, tungsten carbide, and at least one additive compound selected from compounds of transition metals belonging to Groups 4 to 6 of the periodic table, yttrium compounds, scandium compounds, and lanthanoid compounds. This ceramic member has improved durability when used in a cutting tool because at least one selected from transition metals belonging to Groups 4 to 6 of the periodic table, yttrium, scandium, and lanthanoids is distributed in at least one of the first crystal grain boundary (grain boundary between alumina crystal grains and tungsten carbide crystal grains) and the second crystal grain boundary (grain boundary where two alumina crystal grains are in contact). The ceramic member disclosed in Patent Document 1 includes a substrate and a coating layer formed on the surface of the substrate. By providing the coating layer, the oxidation resistance and hardness of the ceramic member can be improved, and the durability of the ceramic member can be improved. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-113320 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a demand for high efficiency in cutting, and the load that the cutting tool receives from the workpiece during cutting is increasing. In response to the increase in the load that the cutting tool receives from the workpiece, there is a demand for improvement in the adhesion between the substrate and the coating layer. The present disclosure has been made in consideration of the above-mentioned circumstances, and aims to improve the adhesion between a substrate and a coating layer in a ceramic member, and can be realized in the following forms. [Means for solving the problem]

[0005] [1] A substrate containing alumina and tungsten carbide; A ceramic member having a coating layer formed on a surface of the substrate and made of a compound having a NaCl type crystal structure, When the coating layer was measured by X-ray diffraction, The peak intensity assigned to the (111) plane of the compound is designated as IA, When the peak intensity assigned to the (200) plane of the compound is IB, A ceramic member having a peak intensity ratio (IA / IB) of 1.0 or more.

[0006] [2] The ceramic member according to [1], wherein the coating layer is formed of a compound having a NaCl-type crystal structure containing titanium.

[0007] [3] The ceramic member according to [1] or [2], wherein the coating layer is formed of titanium nitride. [4] The ceramic member according to any one of [1] to [3], wherein the coating layer has a thickness of 0.05 μm or more.

[0008] A cutting insert comprising the ceramic member according to any one of [1] to [4].

[0009] A cutting tool comprising the cutting insert according to [5]. Effect of the Invention

[0010] If the value of the peak intensity ratio (IA / IB) is 1.0 or more, the adhesion between the substrate and the coating layer in the ceramic member is improved. When the cutting insert is made of the above-mentioned ceramic member, the cutting insert has excellent durability. When a cutting tool includes the cutting insert, the cutting tool has excellent durability. [Brief description of the drawings]

[0011] [Figure 1] FIG. 13 is a diagram showing X-ray diffraction patterns of coating layers formed with different bias voltages. [Diagram 2] FIG. 1 is a schematic diagram showing a NaCl type crystal structure. [Diagram 3] 1 is a graph showing calculation results of the bond strength at the interface between a substrate and a coating layer. [Figure 4] FIG. 2 is a plan view of an example of a cutting tool. [Diagram 5] FIG. 2 is a perspective view of an example of a cutting insert. [Figure 6] FIG. 6 is a cross-sectional view taken along line AA in FIG. 5. [Figure 7] 1 is a graph showing the relationship between bias voltage and adhesion strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the present disclosure will be described specifically and in detail for each item. In this specification, when a numerical range is described using "to", the range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".

[0013] 1. Ceramic materials The ceramic member has a base material containing alumina (Al2O3) and tungsten carbide (WC), and a coating layer formed on the surface of the base material and made of a compound having a NaCl type crystal structure. When the coating layer of the ceramic member was measured by X-ray diffraction, The peak intensity assigned to the (111) plane of the compound is designated as IA, When the peak intensity assigned to the (200) plane of the compound is IB, The peak intensity ratio (IA / IB) is 1.0 or more.

[0014] (1) Base material The substrate contains at least alumina and tungsten carbide. The content of each component will be described. The following content is the amount when the entire substrate is taken as 100 vol%. The content of each component in the substrate can be calculated by determining the amount of each element by X-ray fluorescence analysis or the like. The content of tungsten carbide is not particularly limited. From the viewpoints of hardness and sinterability, the content of tungsten carbide is preferably 20 vol% to 95 vol%, more preferably 23 vol% to 64 vol%, and further preferably 33 vol% to 64 vol%. The alumina content is not particularly limited. From the viewpoints of hardness and sinterability, the alumina content is preferably 3 vol% to 74 vol%, more preferably 23 vol% to 64 vol%, and further preferably 33 vol% to 64 vol%.

[0015] The base material may contain other components besides tungsten carbide and alumina. Suitable examples of other components include components containing at least one element selected from the group consisting of Group 3 of the periodic table (including lanthanoids), titanium, zirconium, and hafnium (hereinafter also referred to as "specific element"). Among these components, from the viewpoint of good tool life, components containing at least one element selected from the group consisting of zirconium, yttrium, titanium, hafnium, and ytterbium are preferred. When these other components are contained, the specific element is distributed at the grain boundaries between the tungsten carbide crystal grains and the alumina crystal grains, and between the alumina crystal grains, in the ceramic member made of the base material. In this case, the sinterability is improved, and the bond strength of the grain boundaries is improved. The details of the mechanism by which the bond strength is improved in this way are speculated as follows. That is, tungsten carbide, which is a carbide, and alumina, which is an oxide and is chemically stable, do not react easily, and usually sufficient bond strength is not obtained between the two. However, when the specific element is present at the grain boundaries, the specific element bonds with the oxygen of the alumina, and further, the specific element bonds with the carbon of the tungsten carbide, and as a result, it is speculated that the tungsten carbide and alumina are bonded via the specific element. As a result of the improvement in the bond strength of the grain boundaries, the wear resistance of the ceramic member is improved, and the life of the tool is extended.

[0016] In order to distribute the specific element in the grain boundary, each component may be dispersed well by a method such as bead mill pulverization during the manufacture of the ceramic member. For example, if fine zirconia powder or a zirconium salt solution is used as the zirconia raw material, the zirconium element is effectively distributed in the grain boundary. In addition, it is also effective to use a dispersion mixing process in which only the zirconia raw material is pulverized first, or to use zirconia as the pulverization media. In addition, by optimizing the temperature increase rate and holding time during firing, the movement (diffusion) of a specific element can be promoted.

[0017] The average particle size of each component is not particularly limited, and may be 1.0 μm or less, or 0.7 μm or less. In this specification, the "average particle size" is a value measured by an intercept method based on an image obtained by etching a mirror-polished ceramic member and observing the same with a SEM.

[0018] (2) Covering layer The coating layer is formed of a compound having a NaCl-type crystal structure. A compound having a NaCl-type crystal structure (hereinafter also referred to as a NaCl-type compound) is a compound having a face-centered cubic lattice structure. The coating layer being formed of a NaCl-type compound means, for example, that a peak due to a NaCl-type crystal structure is observed in a diffraction pattern measured by X-ray diffraction of the coating layer. The coating layer is preferably mainly composed of a NaCl-type compound. In addition, when the coating layer is mainly composed of a NaCl-type compound, the peak due to the above-mentioned NaCl-type crystal structure will show the maximum intensity in the diffraction pattern measured by X-ray diffraction.

[0019] From the viewpoint of improving hardness, the compound having a NaCl type crystal structure is preferably a compound having a NaCl type crystal structure containing titanium. The compound having a NaCl type crystal structure containing titanium may be at least one compound selected from titanium nitride (TiN), titanium (Ti) carbonitride, and composite nitride containing titanium (Ti) and aluminum (Al). Among these, from the viewpoint of oxidation resistance, the compound having a NaCl type crystal structure is more preferably titanium nitride.

[0020] The coating layer is formed on the surface of the substrate. The coating layer directly coats the substrate. Another hard layer having a different composition may be provided on the surface of the coating layer. In order to clarify the definition of the wording, in this specification, the layer formed directly on the surface of the substrate is referred to as the coating layer, and the layer formed outside the coating layer is referred to as the hard layer.

[0021] The thickness of the coating layer is not particularly limited. The thickness of the coating layer is preferably 0.02 μm or more, more preferably 0.05 μm or more, and even more preferably 1.0 μm or more. The thicker the coating layer is, the more effective it is in suppressing oxidation of the substrate covered by the coating layer and in improving the hardness of the ceramic member. The thickness of the coating layer is preferably 30.0 μm or less, more preferably 15.0 μm or less, and even more preferably 10.0 μm or less. If the coating layer is below the above upper limit, the adhesion between the coating layer and the substrate can be ensured, and the wear resistance of the ceramic member can be improved. From these viewpoints, the thickness of the coating layer can be 0.02 μm or more and 30.0 μm or less, preferably 0.05 μm or more and 15.0 μm or less, and more preferably 1.0 μm or more and 10.0 μm or less. The thickness of the coating layer can be measured by cutting the ceramic member and observing the cross section with an SEM. The thickness of the coating layer can be controlled, for example, by adjusting the conditions for forming the coating layer. When a hard layer is provided on the outside of the coating layer, the total thickness of the coating layer and the hard layer is 1.0 μm. From the viewpoint of adhesion to the substrate, it is preferably 10.0 μm or less.

[0022] The adhesive strength between the substrate and the coating layer is preferably 1.20 MPa or more, more preferably 1.30 MPa or more. If the adhesive strength is equal to or more than the lower limit above, the adhesiveness between the coating layer and the substrate can be sufficiently ensured. The adhesive strength is usually 2.0 MPa or less. The adhesion strength was measured by scratch testing and the shear stress F was calculated using the following formula: BW In the following formula, the Brunel hardness H of the substrate is b may be calculated by converting the Vickers hardness of the substrate. The adhesive strength can be controlled, for example, by adjusting the bias voltage applied to the substrate as one of the conditions for forming the coating layer.

[0023]

number

[0024] In the ceramic member, the coating layer does not have to cover the entire surface of the base material. In order to increase the durability of the ceramic member, the coating layer may be provided in an area of ​​the ceramic member where oxidation resistance and hardness need to be increased due to high temperatures or strong forces. For example, when the ceramic member is used as a cutting tool, the coating layer may be provided in the area that is in contact with the workpiece and directly involved in cutting, and in the surrounding area that becomes relatively hot.

[0025] (3) Peak intensity ratio (IA / IB) Here, the relation between IA and IB will be explained. The peak intensities IA and IB are obtained by measuring the coating layer by X-ray diffraction. In X-ray diffraction, measurements are performed from the surface side of the coating layer in order to evaluate the orientation state of the NaCl-type compound at the joint surface between the coating layer and the substrate.

[0026] The peak intensity IA is the intensity of the peak assigned to the (111) plane of the NaCl type compound. For example, when the NaCl type compound is titanium nitride, the peak height at about 2θ=36.6° shown in FIG. 1 is preferably used. The peak intensity IB is the intensity of the peak assigned to the (200) plane of the NaCl type compound. For example, when the NaCl type compound is titanium nitride, the peak height in the vicinity of 2θ=42.6° shown in FIG. 1 is preferably used.

[0027] When the coating layer of the ceramic member is measured by X-ray diffraction, the peak intensity ratio (IA / IB) is 1.0 or more, where IA is the peak intensity attributable to the (111) plane of the NaCl type compound and IB is the peak intensity attributable to the (200) plane of the NaCl type compound. The peak intensity ratio (IA / IB) is preferably 2.8 or more, and is usually 5.0 or less. The peak intensity ratio (IA / IB) value represents the ratio of the (111) plane to the (200) plane of the NaCl-type compound at the interface between the coating layer and the substrate. A peak intensity ratio (IA / IB) value of 1.0 or more means that the (111) plane of the NaCl-type compound is preferentially oriented over the (200) plane. By making the peak intensity ratio (IA / IB) value 1.0 or more, the adhesion between the coating layer and the substrate can be improved by electrical interaction.

[0028] In this disclosure, the value of the peak intensity ratio (IA / IB) is important. Here, the reason why the (111) plane of the NaCl type compound contributes to the adhesion at the bonding surface will be explained. An example will be described in which the coating layer is titanium nitride (TiN). Figure 2 is a schematic diagram showing the crystal structure of NaCl type, with black circles representing cations (Ti atoms) and white circles representing anions (N atoms). The left and right figures in Figure 2 show the same crystal structure. The left and right figures are viewed from different angles. In the NaCl type crystal structure, a layer 1 made of cations and a layer 3 made of anions are alternately laminated. The (111) plane is the plane on which either the layer 1 made of cations or the layer 3 made of anions appears. When the interface of the coating layer facing the substrate is the (111) plane and the layer 1 made of cations appears, this interface is an electrically positive polarity interface. When the interface of the coating layer facing the substrate is the (111) plane and the layer 3 made of anions appears, this interface is an electrically negative polarity interface. Therefore, if the interface is a (111) surface, whether layer 1 made of cations or layer 3 made of anions appears at the interface, it will be a polar interface, and it is thought that the electrical interaction will improve the adhesion strength with the substrate. In addition, when the interface of the coating layer facing the substrate is the (200) plane, it is a non-polar interface with a 1:1 composition of cations and anions, and is electrically neutral, so it is thought that the adhesive strength with the substrate is weak. When the interface of the coating layer facing the substrate is the (001) plane, it is also a non-polar interface like the (200) plane, and is electrically neutral, so it is thought that the adhesive strength with the substrate is weak.

[0029] The peak intensity ratio IA / IB can be controlled, for example, by adjusting the bias voltage applied to the substrate when forming the coating layer. Of the three diffraction patterns shown in Fig. 1, the first is a diffraction pattern of the coating layer of Comparative Example 1 with a bias voltage of -50V. The second is a diffraction pattern of the coating layer of Example 1 with a bias voltage of -100V. The third is a diffraction pattern of the coating layer of Example 2 with a bias voltage of -150V. In Fig. 1, the magnitude of the bias voltage is expressed as an absolute value.

[0030] (4) Manufacturing method of ceramic components The method for producing the ceramic member is not particularly limited. For example, a coating layer containing a NaCl type compound can be formed on the surface of the substrate by arc ion plating evaporation. In this production method, the desired ceramic member can be obtained by controlling the conditions for forming the coating layer. When the coating layer is a single layer, one type of target (evaporation source) is used to form the coating layer. An alloy target containing Ti or the like is used as the target, and nitrogen gas or the like can be used as the reactive gas.

[0031] 2. Simulation calculation of interface bond strength (1)Calculation method The bonding strength of the interface is confirmed by theoretical prediction using simulation calculations of electronic states called first-principles calculations. Here, first-principles calculation is a general term for electronic state calculation that does not use any empirical fitting parameters, etc., and is a method that allows electronic state calculations to be performed simply by inputting the atomic numbers and coordinates of each element that constitutes a unit cell or molecule, etc. One of the first-principles calculation methods is the Projector Argmented-Wave (PAW) method. This method has the advantage of being able to perform calculations with high accuracy and in a relatively short time, and it is also possible to calculate the optimization of crystal structures by preparing the potentials of each atom that composes a unit cell and calculating the electronic state. In addition, a calculation method called density functional theory is used to calculate the interactions between the many electrons present in a crystal. One of the approximation methods using density functional theory is called GGA (Generalized Gradient Approximation). By using this method, it is possible to calculate the electronic state with relatively high accuracy. A first-principles calculation package program including these is called the Vienna Ab-initio Simulation Package (VASP). All first-principles calculations in this embodiment are performed using this VASP. Using first-principles calculations, we performed optimization calculations and total energy calculations for the interface and surface structure between the substrate and the coating layer. The total energy Et of the interface obtained by the calculations, the total energy Eslab of the substrate surface when the substrate and the coating layer are separated, and the total energy E of the coating layer surface slab_TiN Furthermore, the bond strength Ws of the interface can be calculated from the cross-sectional area A of the interface. Since the surface of the substrate is composed of alumina crystal grains and tungsten carbide crystal grains, the total energy Eslab of the substrate surface is calculated by multiplying the surface energy E of the alumina crystal grains by the surface energy E of the alumina crystal grains. slab_Al2O3 and the surface energy E of the tungsten carbide crystal grains slab_WC That is, the bond strength Ws of the interface is calculated by formula (1). W S =(E slab_Al2O3 +E slab_WC +E slab_TiN -Et) / 2A...Equation (1)

[0032] Below, a simulation calculation of the interface bond strength Ws will be explained using specific compounds as examples, but the present disclosure is not limited to these examples. To simplify the calculation, the interface bond strength Ws will be calculated for the case where the surface of the substrate is composed only of alumina crystal grains and a titanium nitride coating layer is formed on the surface, and for the case where the surface of the substrate is composed only of tungsten carbide crystal grains and a titanium nitride coating layer is formed on the surface. In the former case, E slab_WC = 0. In the latter case, Eslab_Al2O3 =0.

[0033] (2) Calculation results For the structural model of the Al2O3(001) / TiN(001) interface, an initial structural model is determined taking into account the end structure and lattice mismatch rate. For the initial structural model, the rigid body displacement and end structure are taken into account to obtain the most stable structure. The total energy of the interface model having the obtained most stable structure and equation (1) are used to calculate the bond strength Ws of the interface. The most stable structure is obtained for the WC(001) / TiN(001) interface structure model in the same manner as above. The total energy of the interface model having the most stable structure obtained is used to calculate the bond strength Ws of the interface using equation (1).

[0034] For the structural model of the Al2O3(001) / TiN(111) interface, an initial structural model is determined taking into account the end structure and lattice mismatch rate. For the initial structural model, the rigid body displacement and end structure are taken into account to obtain the most stable structure. The total energy of the interface model having the obtained most stable structure and the bond strength Ws of the interface are calculated using equation (1). The most stable structure is obtained for the WC(001) / TiN(111) interface structure model in the same manner as above. The total energy of the interface model having the most stable structure obtained is used to calculate the bond strength Ws of the interface using equation (1).

[0035] The calculation results of the interface bond strength Ws for each interface structural model are shown in Figure 3. From these results, it can be seen that for both alumina and tungsten carbide, the interface bond strength Ws is higher when the titanium nitride (111) plane is the interface than when the titanium nitride (001) plane is the interface. Titanium nitride is an example of a compound having a NaCl-type crystal structure. The (001) plane in the NaCl-type crystal structure is equivalent to the (200) plane in the NaCl-type crystal structure, and is an electrically neutral plane. Simulation calculation results of the bond strength of the interface support the idea that the adhesion between the coating layer and the substrate can be improved by making the peak intensity ratio (IA / IB) value 1.0 or more. The bond strength Ws between the substrate and coating layer in an actual ceramic member is obtained by calculation taking into consideration the area ratio of alumina crystal grains to tungsten carbide crystal grains on the surface of the substrate.

[0036] 3.Cutting tools The cutting tool of the present disclosure uses the ceramic member of the present disclosure described above. The shape and size of the cutting tool can be appropriately changed depending on the application, etc. An example of a cutting tool will be illustrated and described. Fig. 4 shows a cutting tool 110. Figs. 5 and 6 show a cutting insert made of a ceramic member 101. The ceramic member 101 has a substrate 102 and a coating layer 103. The cutting tool 110 includes a holder 111 having a presser plate 112, and the ceramic member 101 (cutting insert) set by the presser plate 112. EXAMPLES

[0037] The present disclosure will be explained more specifically with reference to examples.

[0038] 1. Manufacturing of ceramic components (1) Preparation of substrate The substrate of the ceramic member was prepared by the following procedure. First, alumina, tungsten carbide, and a compound containing a specific element, which are the raw materials of the substrate, were prepared. Each raw material of the substrate was prepared in the form of powder. As a specific example, alumina powder with an average particle size of about 0.5 μm, tungsten carbide powder with an average particle size of about 0.7 μm, and zirconia powder with an average particle size of about 0.7 μm were used. Note that these average particle sizes are merely examples and can be changed as appropriate. The average particle size of each powder can be measured using a laser diffraction type particle size distribution measuring device. In addition, the zirconia powder is preferably zirconia powder (3YSZ powder) partially stabilized with 3 mol% yttria (Y2O3) as a stabilizer.

[0039] Next, the prepared raw materials were weighed, mixed with 55 vol% alumina powder and 45 vol% tungsten carbide powder, and then 0.8 mol% (less than 1 vol% in terms of volume ratio) zirconia powder was added and mixed. Then, preliminary mixing and grinding was performed. Specifically, a ball mill was used to grind the particles of each powder while mixing [1] alumina powder, [2] tungsten carbide powder, and [3] a solution containing zirconium ions together with [4] a solvent. The solution of [3] is, for example, a 85% zirconium (IV) butoxide 1-butanol solution. The solvent of [4] is, for example, ethanol. The time for carrying out the preliminary grinding is about 20 hours. The time for carrying out the preliminary grinding is not particularly limited, and may be less than 20 hours or may be longer than 20 hours.

[0040] Next, a slurry was obtained by mixing and grinding. Specifically, zirconia and a solvent were added to the mixture in the ball mill, and further mixing and grinding were performed. As a result, a slurry in which alumina, tungsten carbide, and zirconia particles were dispersed was obtained. The time for adding zirconia and further mixing and grinding was about 20 hours. The time for mixing and grinding is not particularly limited, and may be less than 20 hours or may be longer than 20 hours. Next, the slurry was dried to prepare a mixed powder. The mixed powder can be obtained from the slurry by, for example, drying the slurry in a hot water bath to remove the solvent from the slurry to obtain a powder, and then passing the obtained powder through a sieve.

[0041] Finally, ceramic members were produced from the mixed powder by hot pressing. In the hot press, the mixed powder was filled into a carbon mold and heated while being uniaxially pressurized. This resulted in a ceramic member, which was a sintered body of the mixed powder. The hot pressing conditions were as follows: sintering temperature 1750°C, sintering time 2 hours, pressure 30 MPa, and atmospheric gas argon (Ar).

[0042] (2) Preparation of the coating layer After preparing the substrate, a coating layer was formed on the surface of the substrate, completing the ceramic member. A cathode arc ion plating device was used to form the coating layer. The pressure in the chamber was reduced by a vacuum pump, and the substrate was heated to a temperature of 500°C by a heater installed in the device, and the pressure in the chamber was 4.0×10 -3 The vacuum was drawn until the pressure in the chamber reached 1.0 Pa. Next, argon gas was introduced to maintain the pressure in the chamber at 1.0 Pa, and the voltage of the bias power supply applied to the substrate was gradually increased to -350 V, and the surface of the substrate was cleaned for 20 minutes. Then, the argon gas was exhausted. Next, an alloy target containing a coating layer composition was set in the above device, and while introducing nitrogen gas as a reactive gas, an arc current of 100 A was supplied to the cathode electrode while maintaining the substrate temperature at 500 ° C, the reactive gas pressure at 1.0 Pa, and the bias voltage of the substrate at -50 to -150 V, and metal ions were generated from the arc type evaporation source to form a 1.5 μm coating layer on the cutting edge. In this embodiment, an evaporation source was used in which the magnetic field lines extended to the substrate and the plasma density of the film-forming gas near the substrate was significantly higher than that of a conventional evaporation source. Comparative Example 1 was produced under the above coating conditions with a bias voltage set at -50V, while Examples 1 and 2 were produced under the above coating conditions with a bias voltage set at -100V and -150V, respectively.

[0043] 2.X-ray diffraction The obtained coating layer was measured using an X-ray diffractometer (Rigaku RINT-TTR3) using Cu-Kα radiation. The measurement results are shown in Figure 1. From the measurement results, the peak intensity IA assigned to the (111) plane of the NaCl type compound and the peak intensity IB assigned to the (200) plane of the NaCl type compound were obtained. In Comparative Example 1, the peak intensity IA attributable to the (111) plane of the NaCl type compound was smaller than the peak intensity IA attributable to the (200) plane of the NaCl type compound. The IA / IB value was 0.65, that is, the IA / IB ratio in Comparative Example 1 was smaller than 1.0. In Example 1, the peak intensity IA attributable to the (111) plane of the NaCl type compound was equal to the peak intensity IA attributable to the (200) plane of the NaCl type compound, i.e., the IA / IB ratio in Example 1 was 1.0. In Example 2, the peak intensity IA attributable to the (111) plane of the NaCl type compound was greater than the peak intensity IA attributable to the (200) plane of the NaCl type compound. The IA / IB value was 2.8, i.e., in Example 2, the IA / IB ratio was greater than 1.0.

[0044] 3. Scratch test A scratch test was performed to calculate the adhesion strength (MPa) for Examples 1 and 2 and Comparative Example 1. For each of Examples 1 and 2 and Comparative Example 1, the adhesion strength of five samples was measured, and the average value was taken as the adhesion strength for each example. The conditions for the scratch test are as follows. Scratch Tester:Revetest Scratch Tester Table speed: 10mm / min Load speed: 100N / min Indenter (diamond) curvature radius: 0.2 mm Specific measurement conditions: The position where the coating layer peeled off was detected with an optical microscope, and the adhesion strength was measured from the distance between the peeled position and the position where the load application was started.

[0045] The adhesion strengths of Examples 1 and 2 and Comparative Example 1 are shown in the graph of FIG. From these results, it was confirmed that Examples 1 and 2, in which IA / IB is 1.0 or more, had higher adhesion strength than Comparative Example 1. In particular, Example 2, in which IA / IB is 2.8 or more, had higher adhesion strength than Comparative Example 1.

[0046] 4.Cutting test In Example 2 (bias voltage: -150V), the ceramic members of Samples 1 to 6, in which the material and thickness (μm) of the coating layer were changed as shown in Table 1, were processed into cutting inserts to prepare cutting tools. All of Samples 1 to 6 have an IA / IB ratio of 1.0 or more. Cutting tests were performed using the cutting tools of Samples 1 to 6. In the cutting tests, the machining distance (cutting distance) until chipping occurred in the cutting tools was measured and evaluated as durability. The shape of the cutting tools prepared from each sample is a shape specified by the designation "CNGA / N120408-TNBE" in accordance with the Japanese Industrial Standard JIS B4120. Hardened steel (SCM415 / HRC63) was used as the workpiece to be cut in the cutting tests. The cutting test conditions are as follows: Cutting speed: 200m / min Depth of cut: 0.2mm Feed rate: 0.20mm / revolution Cooling water: dry The evaluation criteria for the processing distance are as follows: "A (Excellent)": Processing distance is 1.6km or more, "B (Good)": Processing distance is 1.1 km or more and less than 1.6 km, "C (OK)": Processing distance is 0.7km or more and less than 1.1km, "D (Poor)": Machining distance is less than 0.7km.

[0047] The results of the cutting tests are shown in Table 1.

[0048] [Table 1]

[0049] From the results in Table 1, it was confirmed that Samples 1 to 6, in which IA / IB is 1.0 or more, had a machining distance of 0.7 km or more in the cutting test, and thus had excellent durability as cutting tools. It was confirmed that, among Samples 1 to 6, Samples 1 and 3 to 6, which have a coating layer thickness of 0.05 μm or more, have improved durability of the cutting tool.

[0050] 5. Effects of the embodiment In the examples in which the peak intensity ratio (IA / IB) was 1.0 or more, the adhesion between the substrate and the coating layer in the ceramic member was improved compared to the comparative examples. The cutting insert (cutting tool) made of the ceramic member of the above embodiment has excellent durability.

[0051] <Other embodiments (modifications)> The present invention is not limited to the above examples and embodiments, and can be embodied in various forms without departing from the spirit and scope of the present invention. In the above examples, TiN, TiCN, and TiAlN are exemplified as at least one compound having a NaCl-type crystal structure, but the coating layer may contain two or more of these, or may contain other compounds having a NaCl-type crystal structure. [Explanation of symbols]

[0052] 1...Cation-based layer 3...Anion layer 101...Ceramics member (cutting insert) 102...Base material 103…Covering layer 110...Cutting tools 111…Holder 112...Press foot

Claims

1. A substrate containing alumina and tungsten carbide; A ceramic member having a coating layer formed on a surface of the substrate and made of a compound having a NaCl type crystal structure, When the entire base material is taken as 100 vol%, The content of the alumina is 3 vol% to 64 vol%; The content of the tungsten carbide is 33 vol% to 95 vol%; When the coating layer was measured by X-ray diffraction, The peak intensity assigned to the (111) plane of the compound is designated as IA, When the peak intensity assigned to the (200) plane of the compound is IB, The peak intensity ratio (IA / IB) is 1.0 or more, A ceramic member characterized in that the adhesion strength calculated by carrying out a scratch test under the following conditions is 1.20 MPa or more. (conditions) Scratch tester: Revetest Scratch Tester Table speed: 10 mm / min Load speed: 100N / min Indenter (diamond) curvature radius: 0.2 mm Specific measurement conditions: The position where the coating layer peeled off was detected using an optical microscope, and the adhesion strength was measured from the distance between the peeled position and the position where the load was started.

2. 2. The ceramic member according to claim 1, wherein the coating layer is formed of a titanium-containing compound having a NaCl-type crystal structure.

3. 3. The ceramic member according to claim 1, wherein the coating layer is made of titanium nitride.

4. The ceramic member according to claim 1 , wherein the coating layer has a thickness of 0.05 μm or more.

5. A cutting insert comprising the ceramic member according to any one of claims 1 to 4.

6. A cutting tool comprising the cutting insert according to claim 5.

Citation Information

Patent Citations

  • Cutting tool made of surface coated tungsten carbide-based cemented carbide

    JP1990159363A

  • Method for authenticating person

    JP1999003320A

  • Surface coated member and surface coated cutting tool

    JP2006281363A

  • Ceramic sintered body, coated ceramic sintered body, cut insert and cutting tool

    JP2010234508A

  • Ceramic member and cutting tool

    JP2016113320A